2011
DOI: 10.4314/ejhs.v19i2.69421
|View full text |Cite
|
Sign up to set email alerts
|

A 2-year review of ocular trauma in Jimma University Specialized Hospital

Abstract: BACKGROU D: Ocular trauma is an important public health hazard with enormous human, social and economical consequences. Worldwide, there are about 1.6 million blind and 19 million with unilateral visual loss people from eye injuries. A study done at a teaching referral hospital in Addis Ababa revealed 15.8% of blindness to be attributed to trauma alone. But there are no researches done on patterns of ocular trauma in the study area. Thus, the objective of this study was to determine the pattern of ocular traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 25 publications
2
18
2
Order By: Relevance
“…12 In our study, right eye was involved in 45% cases whereas left eye was involved in 55% cases. This didn't show significant association between the involvement of either eye.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations
“…12 In our study, right eye was involved in 45% cases whereas left eye was involved in 55% cases. This didn't show significant association between the involvement of either eye.…”
Section: Discussionsupporting
confidence: 44%
“…Whereas in JUDO Study it showed closed globe injuries (45.4%) were encountered more than open globe injuries (22.71%). 12 In our study, we found a significant association between the duration of presentation and presence of complications at presentation (Chi-square value 18.2, degree of freedom= 3, p. value= 0.001) which may affect final visual outcome. Two weeks after the treatment, the final visual outcome was analysed which was difficult to analyse in 16 (10.66%) cases and was not documented in 6 (4%) cases as they were not cooperative.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…[8][9][10] Out of 1259 patients 8.02% patients were pseudophakic both eyes. Most of them came for refraction and some of them came with nonspecific complaints.…”
Section: Discussionmentioning
confidence: 99%